A Forkhead Transcription Factor Is Important for True Hyphal as well as Yeast Morphogenesis in Candida albicans - Bensen, Eric S. (American Society for Microbiology, 2002)
Candida albicans is an important pathogen of immunocompromised patients which grows with true hyphal, pseudohyphal, and yeast morphologies. The dynamics of cell cycle progression are markedly different in true hyphal relative to pseudohyphal and yeast cells, including nuclear movement and septin ring positioning. In Saccharomyces cerevisiae, two forkhead transcription factors (ScFKH1 and ScFKH2) regulate the expression of B-cyclin genes. In both S. cerevisiae and Schizosaccharomyces pombe, forkhead transcription factors also influence morphogenesis. To explore the molecular mechanisms that connect C. albicans morphogenesis with cell cycle progression, we analyzed CaFKH2, the single homolog of S. cerevisiae FKH1/FKH2. C. albicans cells lacking CaFkh2p formed constitutive pseudohyphae under all yeast and hyphal growth conditions tested. Under hyphal growth conditions levels of hyphae-specific mRNAs were reduced, and under yeast growth conditions levels of several genes encoding proteins likely to be important for cell wall separation were reduced. Together these results imply that Fkh2p is required for the morphogenesis of true hyphal as well as yeast cells. Efg1p and Cph1p, two transcription factors that contribute to C. albicans hyphal growth, were not required for the pseudohyphal morphology of fkh2 mutants, implying that Fkh2p acts in pathways downstream of and/or parallel to Efg1p and Cph1p. In addition, cells lacking Fkh2p were unable to damage human epithelial or endothelial cells in vitro, suggesting that Fkh2p contributes to C. albicans virulence.